A Retrospective Study on Incidence of Neoplasms in Canine Population around Anand, Gujarat - Asodiya, Foram A; Hadiya, Kamlesh K; Patel, Ashish C; Parmar, Jignesh J; Mahla, Jalendra K; Parikh, Pinesh V (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The incidences of canine neoplasms were calculated retrospectively from 23,236 cases presented at Teaching Veterinary Clinical Complex,  Anand (Gujarat, India) during January, 2017 to December, 2021. In all 562 cases had canine neoplasms, which included mammary tumors  322 (57.29%), oral tumors 59 (10.49%), bone tumors 36 (6.41%), CTVT 68 (12.09%) and other tumors 77 (13.70%). Further in prospective  study of 11,178 canine cases from January, 2022 to December, 2023, a total of 152 cases were diagnosed and treated for neoplasms.  Out of which 71 cases were of mammary gland tumors, 36 cases of oral tumors, 22 cases of CTVT, and rest others. In retrospective and  prospective studies, the highest incidence of canine mammary tumors was observed in the age group of 8 to 12 years, whereas no  case was reported below 4 years of age. The incidences of canine neoplasms were significantly higher in female than in male dogs  mainly due to high level of neoplasms in the mammary gland and CTVT in females. The breed most vulnerable to the neoplasms was  Labrador retriever, whereas the least tumors were found in Rottweiler. The age, breed, and sex were identified as the major risk factors  for tumorogenesis in canines.
Keywords: Bone tumor; Canine neoplasm; Incidence; Mammary tumor; Oral tumor